Revisiting the Relationship Between Financial Performance, ESG, and Firm Value: Evidence from Indonesian Non-Financial Listed Firms - Agung Dinarjito; Zef Arfiansyah; Sandi Setiadi (Ilomata International Journal of Tax and Accounting, 2026)
Environmental, social, and governance (ESG) performance has received growing attention from investors, regulators, and corporate managers as sustainability considerations become increasingly integrated into business decision-making. However, evidence regarding the relationship between ESG performance and firm value remains inconclusive, particularly in emerging markets. Moreover, previous studies have typically examined financial performance and ESG performance separately or focused exclusively on either aggregate ESG scores or individual ESG dimensions, limiting a comprehensive understanding of their relative importance in explaining firm value. This study investigates the influence of profitability, liquidity, solvency, firm growth, aggregate ESG performance, and the environmental, social, and governance dimensions on the firm value of Indonesian non-financial listed companies. Using panel data from 69 firms listed on the Indonesia Stock Exchange during 2022–2024, comprising 207 firm-year observations, the study employs a Random Effect Model with robust standard errors. Firm value is measured using the natural logarithm of share price (LnMV), while ESG data are obtained from Refinitiv. The results indicate that sales growth, as a proxy for firm growth, is the only variable positively and significantly associated with firm value. In contrast, profitability, liquidity, solvency, aggregate ESG performance, and the individual ESG dimensions do not exhibit statistically significant relationships with firm value. These findings suggest that investors place greater emphasis on firms’ growth prospects than on conventional financial indicators or ESG-related information when valuing Indonesian non-financial firms. The study contributes to the literature by providing recent evidence from an emerging-market context and by simultaneously evaluating financial performance, aggregate ESG performance, and individual ESG dimensions within a unified empirical framework.